UPAYA DALAM PENEGAKAN HUKUM PIDANA OLEH POLRI HUBUNGAN DENGAN LOCUS DELICTI YANG BELUM DIKETAHUI SECARA PASTI - A.MUH. AQSHA. ISHAK (Universitas 17 Agustus 1945 Samarinda, 2017)
ABSTRACTThe relationship between reconstruction with the crime scene is to justify the information of the suspect made by the investigator in the context of criminal investigation activities to be adapted to the actual scene of the scene. In practice, reconstruction is not done at the actual scene. This is solely done for the security of the suspects themselves in order to avoid the rampage of the public. In addition to that, also to minimize the cost of reconstruction may be less so if the scene where the reconstruction will be held outside the city. But if the crime scene is not located outside the city, the implementation of reconstruction will still be carried out at the actual TKP. If the crime scene is not known with certainty then the efforts undertaken are: Conduct action by means of investigation which is a technique of investigation for the criminal case was revealed, where with this investigation technique will be obtained answers to questions in the field of investigation criminal case; Conducting interrogation activities against the incident reporter and requesting information from witnesses of the witness, expert witnesses and witnesses who know the first case of this criminal case. Although there is a difference in the area between the scene of the case and the area where the victim was found or the result of the crime does not prevent the police to disclose the criminal case, because although there are differences in the area the police still can work together with each other.